The Effectiveness of Using the Visme Platform as a Learning Media to Improve the Learning Outcomes of Cultural Arts for 8th Grade Students at MTs Negeri 1 Sidenreng Rappang - Fhina Silpia; Abd kahar; Zulkifli N N; Muhammad Takdir (Universitas Muhammadiyah Enrekang, 2025)
This study aims to determine the effectiveness of using the Visme platform as a learning media to improve the learning outcomes of Cultural Arts for 8th-grade students at MTs Negeri 1 Sidenreng Rappang. This research is an experimental study with a one-group pretest-posttest design. The population of this study consists of all 8th-grade students at MTs Negeri 1 Sidenreng Rappang, totaling 263 students. The sample was determined using a random sampling technique. The research sample is class VIII.C, consisting of 30 students, and data was collected through multiple-choice tests and questionnaires to measure student learning outcomes, including mastery of learning and the timeliness in receiving the material. The results of the study show that the use of the Visme learning media is effective in improving the learning outcomes of Cultural Arts for students in class VIII.C at MTs Negeri 1 Sidenreng Rappang. This is indicated by the paired sample T-test results, comparing pretest and posttest data, which show a significant value. Based on the analysis of the data, the average pretest score was 37.17, while the posttest score was 86.00. The N-gain test showed an average N-gain value of 76.35%. From the results of the average scores and the N-gain test, it can be concluded that learning Cultural Arts using Visme is effective in improving the learning outcomes of students in class VIII.C at MTs Negeri 1 Sidenreng Rappang.